Lacticaseibacillusparacasei BNCC345679 revolutionizes DSS-induced colitis and modulates gut microbiota - Ahmad, Waqar; Din, Ahmad Ud; Khan, Taj Malook; Rehman, Mujeeb Ur; Hassan, Adil; Aziz, Tariq; Alharbi, Metab; Wu, Jianbo (Frontiers in Microbiology, 2024)
The Gut microbiota plays an important role in the disease progression of inflammatory bowel disease. Although probiotics are effective against IBD, not many studies have investigated their effects on gut microbiota composition and immunomodulation in mouse colitis models. Our study aimed at the therapeutic effects of Lacticaseibacillus paracasei BNCC345679 for the first time and explored its impact on gut microbiome dysbiosis, inflammatory cytokines, related miRNAs, VCAM-1, oxidative stress, intestinal integrity, and mucus barrier. We found that oral intervention of L. paracasei BNCC345679 affects recovering beneficial microbial taxa, including lactobacillus spp and akkermansia spp, followed by improved body weight, DAI score, and inflammatory cytokines. L. paracasei BNCC345679 mitigated oxidative stress and increased the expression of intestinal integrity proteins MUC2 and ZO-1. These results suggested that L. paracasei BNCC345679 has the capacity to reduce DSS-induced colitis and has the potential as a supplement for the mitigation of IBD.